Analysis of the Influence of the Board of Directors, Company Size, Management Ownership, and Kap Audit on the Financial Performance of Bank Perkreditan Rakyat (BPR) - Riwandari Juniasti (Eduvest - Journal of Universal Studies, 2022)
This study aims to analyze the effect of the board of directors, firm size, managerial ownership, and audit of KAP (Public Accounting Firm) audit on the financial performance of Bank Perkreditan Rakyat(BPR). This type of research is associative research. In this study, the population of rural banks located in the Bekasi area was used. The data obtained is based on financial reports that have been published on the website of the Financial Services Authority (www.ojk.go.id) for the period 2018-2021. The data obtained from the results of the study were analyzed using multiple linear regression analysis models using the Eview 10 software program. The results showed that the KAP audit variable had a significant influence on the return on assets of rural banks in the Bekasi area. This is because the resulting p-value is smaller than 0.05. Then the firm size variable significantly affects non-performing loans with a negative relationship direction. The KAP audit variable was also proven to have a significant effect on non-performing loans with a similar direction, namely negative. Both are able to affect non-performing loans because the p-value obtained is smaller than 0.05. Simultaneously also found the effect of the board of directors, company size, managerial ownership, and KAP audits on the return on assets or non-performing loans of BPRs in the Bekasi area for the 2018-2021 period.